Antimicrobial susceptibility of Streptococcus pneumoniae isolated from patients in the northeastern macroregion of São Paulo state, Brazil, 1998-2013 - Marta Inês C. Medeiros; Samanta Cristine G. Almeida; Sérgio Bokermann; Evandro Watanabe; Maria Luiza L. S. Guerra; Denise de Andrade (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introdution: There are reports worldwide about the increase in infections caused by Streptococcus pneumoniae resistant to antimicrobials. Objective: Evaluate the susceptibility profile of serotypes of Streptococcus pneumoniae associating them with pneumococcal invasive diseases (PID), as well as antimicrobial therapies. Method: This is a retrospective cross-sectional research involving secondary data from 1998 to 2013, in the northeastern macroregion of São Paulo state, Brazil, composed of Araraquara, Barretos, Franca and Ribeirão Preto regions, with 90 municipalities. At Instituto Adolfo Lutz (IAL), isolated strains from patients with PID were subjected to identification, serotyping and antimicrobial susceptibility testing. Results: From 796 strains analyzed, 14.8% (n = 118) were resistant to penicillin, being 3% (n = 24) with intermediate resistance and 11.8% (n = 94) with full resistance, especially in patients with meningitis. Moreover, resistance to ceftriaxone was 5.3%: 34 (4.3%) with intermediate resistance and 8 (1%) with full resistance. We point out that the greatest level of resistance profiles was observed against sulfamethoxazole/trimethoprim (SMT): 350 (49.4%). On the other hand, antimicrobial susceptibility was described above 90% to chloramphenicol: 99.6% (n = 696), erythromycin: 94.7% (n = 664), ceftriaxone: 94.7% (n = 754) and fully susceptible to vancomycin. Among the 18 most common serotypes, 9V and 14 showed less susceptibility to SMT, to penicillin and ceftriaxone; 19A to SMT and penicillin; 1 to SMT; 12F and 3 to chloramphenicol; 6A to SMT; 6B 23F to erythromycin and penicillin. Conclusion: Monitoring of Streptococcus pneumoniae antimicrobial resistance is essential to guide the appropriate empirical treatment of pneumococcal disease.